Will The Income Of Womenpreneurs, Family Size, Husband's Income, Wife's Income, And Children's Income Affect Family Economic Improvement: An Islamic Economic Perspective? - Marlina, Lilis; Ariska Ramadhan, Risca (Publisher Cv. Inara, 2024)
This study aims to explore whether the income of womenpreneurs, family size, husband's income, wife's income, and children's income influence the improvement of family economics from an Islamic economic perspective. It is also hoped that the research can provide recommendations for women to understand and consider Islamic economic principles before deciding to become womenpreneurs and for husbands to consider Islamic Sharia principles when giving permission to wives and children to work. The research method used is quantitative, with a population of 1,898 people and a sample of 95 people obtained through the distribution of questionnaires. The results of the study show that: a) Womenpreneur income has an impact on improving family economics in Dompu Regency from an Islamic economic perspective; b) Family size influences family economic improvement in Dompu Regency from an Islamic economic perspective; c) Husband's income affects family economic improvement in Dompu Regency from an Islamic economic perspective; d) Wife's income contributes to family economic improvement in Dompu Regency from an Islamic economic perspective;e) Children's income has an impact on family economic improvement in Dompu Regency from an Islamic economic perspective.